2014 37th International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO) 2014
DOI: 10.1109/mipro.2014.6859746
|View full text |Cite
|
Sign up to set email alerts
|

Application of the NOK method in sentence modelling

Abstract: Knowledge representation is one of the areas covered by artificial intelligence. One of the methods for graphical representation of text expressed knowledge is the method NOK (Nodes Of Knowledge). NOK method enables transformation of text expressed knowledge into a graphical network of words and group of words. In this paper application of NOK method is presented. This application is based on sentences from an Aesop's Fable in Croatian ("Golden eggs in the chicken") and English ("The Goose with the golden eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…One fable in two languages translated by two different authors is shown in [16]. A knowledge network is created for these translations using the NOK method.…”
Section: Research Motivationmentioning
confidence: 99%
“…One fable in two languages translated by two different authors is shown in [16]. A knowledge network is created for these translations using the NOK method.…”
Section: Research Motivationmentioning
confidence: 99%
“…Initial research [12][13][14] showed that it is possible to model sentences in natural language using conceptual framework NOK. Additional research showed that NOK is applicable in different languages, without adaptation of algorithms of the question answering (QA) system, under condition that rules are well defined [15].…”
Section: Introduction and Related Workmentioning
confidence: 99%